Low-Molecular-Weight Heparin and Recurrent Placenta-Mediated Pregnancy Complications: A Meta-analysis of Individual Patient Data From Randomised Controlled Trials. Issue 3 (March 2017) - Rodger, Marc A.; Gris, Jean-Christophe; de Vries, Johanna I. P.; Martinelli, Ida; Rey, Évelyne; Schleussner, Ekkehard; Middeldorp, Saskia; Kaaja, Risto; Langlois, Nicole J.; Ramsay, Timothy; Mallick, Ranjeeta; Bates, Shannon M.; et al.
Abstract : (Abstracted from Lancet 2016;388:2629–2641) Placenta-mediated pregnancy complications include pre-eclampsia, birth of a small-for-gestational-age neonate, placental abruption, or late pregnancy loss and lead to maternal and fetal or neonatal morbidity and mortality. These complications have a high risk of recurring in subsequent pregnancies, and effective preventive measures are lacking.